Optimizing robot motion for robotic ultrasound-guided radiation therapy. (4th October 2019) - Schlüter, Matthias; Fürweger, Christoph; Schlaefer, Alexander
Abstract: An important aspect of robotic radiation therapy is active compensation of target motion. Recently, ultrasound has been proposed to obtain real-time volumetric images of abdominal organ motion. One approach to realize flexible probe placement throughout the treatment fraction is based on a robotic arm holding the ultrasound probe. However, the probe and the robot holding it may obstruct some of the beams with a potentially adverse effect on the plan quality. This can be mitigated by using a kinematically redundant robot, which allows maintaining a steady pose of the ultrasound probe while moving its elbow in order to minimize beam blocking. Ultimately, the motion of both the beam source carrying and the ultrasound probe holding robot contributes to the overall treatment time, i.e. beam delivery and robot motion. We propose an approach to optimize the motion and coordination of both robots based on a generalized traveling salesman problem. Furthermore, we study an application of the model to a prostate treatment scenario. Because the underlying optimization problem is hard, we compare results from a state-of-the-art heuristic solver and an approximation scheme with low computational effort. Our results show that integration of the robot holding the ultrasound probe is feasible with acceptable overhead in overall treatment time. For clinically realistic velocities of the robots, the overhead is less than 4% which is a small cost for the added benefit of continuous, volumetric, and non-ionizing tracking of organ motion over periodic x-ray-based tracking.